Community-based monitoring of safe motherhood in the United Republic of Tanzania - Mswia Robert; Lewanga Mary; Moshiro Candida; Whiting David; Wolfson Lara; Hemed Yusuf; Alberti K.G.M.M; Kitange Henry; Mtasiwa Deo; Setel Philip (The World Health Organization, 2003)
OBJECTIVE: To examine the progress made towards the Safe Motherhood Initiative goals in three areas of the United Republic of Tanzania during the 1990s. METHODS: Maternal mortality in the United Republic of Tanzania was monitored by sentinel demographic surveillance of more than 77 000 women of reproductive age, and by prospective monitoring of mortality in the following locations: an urban site; a wealthier rural district; and a poor rural district. The observation period for the rural districts was 1992-99 and 1993-99 for the urban site. FINDINGS: During the period of observation, the proportion of deaths of women of reproductive age (15-49 years) due to maternal causes (PMDF) compared with all causes was between 0.063 and 0.095. Maternal mortality ratios (MMRatios) were 591-1099 and maternal mortality rates (MMRates; maternal deaths per 100 000 women aged 15-49 years) were 43.1-123.0. MMRatios in surveillance areas were substantially higher than estimates from official, facility-based statistics. In all areas, the MMRates in 1999 were substantially lower than at the start of surveillance (1992 for rural districts, 1993 for the urban area), although trends during the period were statistically significant at the 90% level only in the urban site. At the community level, an additional year of education for household heads was associated with a 62% lower maternal death rate, after controlling for community-level variables such as the proportion of home births and occupational class. CONCLUSION: Educational level was a major predictor of declining MMRates. Even though rates may be decreasing, they remained high in the study areas. The use of sentinel registration areas may be a cost-effective and accurate way for developing countries to monitor mortality indicators and causes, including for maternal mortality.